MYRICETIN NANO-PHYTOSOMES PEEL-OFF GEL MASK FORMULATION AS ANTIOXIDANT - PURNAMASARI, NUR AINI DEWI; DZAKWAN, MUHAMMAD; PRAMUKANTORO, GANET EKO; MAULUDIN, RACHMAT; ELFAHMI (International Journal of Applied Pharmaceutics, 2021)
Objective: Peel-off gel mask is an alternative preparation which can increase the convenience of use and is expected to increase the antioxidant activity of myricetin nano-phytosomes. Myricetin has various activities, namely as a natural antioxidant, anti-inflammatory, allergy, and anti-cancer. This study aims to determine the nano-phytosome myricetin can be formulated into a gel peel-off mask, determine the concentration of PVA which has the best physical properties of the gel peel-off mask, and determine the antioxidant activity. Methods: The thin layer hydration method was used to manufacture Myricetin nano-phytosomes, then dried using the freeze-drying method. The resulting nano-phytosome characterization included particle size, polydispersion index, zeta potential and absorption efficiency. Peel-off gel mask were made with variations in the concentration of the PVA gelling agent, namely F1 3.5%, F2 7%, F3 14%. The resulting peel-off gel mask was tested for physical quality including organoleptic test, homogeneity, pH, viscosity, adhesion, drying time and testing for antioxidant activity. Results: The resulting peel-off gel mask has the good physical quality and met the existing requirements, where the different PVA concentrations resulted in different physical qualities, the higher the PVA, the faster the dry time. All three formulas exhibited very strong antioxidant activity based on DPPH assay with IC50 value of 14.8 ppm (F1), 15.37 ppm (F2), and 15.87 ppm (F3). Conclusion: Myricetin nano-phytosomes can be formulated into a gel peel-off mask, Formula 2 with a 7% concentration of PVA produces the best physical quality of the peel-off gel mask, the three gel peel-off mask formulas have excellent antioxidant activity.